2015
DOI: 10.1111/anae.13065
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care practices in brain death diagnosis and organ donation

Abstract: Summary We conducted a multicentre study of 1844 patients from 42 Spanish intensive care units, and analysed the clinical characteristics of brain death, the use of ancillary testing, and the clinical decisions taken after the diagnosis of brain death. The main cause of brain death was intracerebral haemorrhage (769/1844, 42%), followed by traumatic brain injury (343/1844, 19%) and subarachnoid haemorrhage (257/1844, 14%). The diagnosis of brain death was made rapidly (50% in the first 24 h). Of those patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
3
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 40 publications
4
59
3
11
Order By: Relevance
“…In our study the length of ICU stay was < 48 hours in 47% of cases after brain death diagnosis whereas in a study done by Escudero D et al 28 , 50% of cases had length of stay was ≤ 24 hours.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…In our study the length of ICU stay was < 48 hours in 47% of cases after brain death diagnosis whereas in a study done by Escudero D et al 28 , 50% of cases had length of stay was ≤ 24 hours.…”
Section: Discussioncontrasting
confidence: 73%
“…Length of ICU stay depended on severity (GCS) at admission: as severity increased, the length of stay decreased. In the study done by Escudero 28 showed GCS was ≤ 8/15 in 91% of the patients admitted and patients deteriorated to brain death (50% in the first 24 h).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a recent Spanish study, 56% of brain death was by CVA and 19% was by traumatic brain injury. 22 In our study, 5% of kidneys were discarded after they were retrieved. Klein and associates reported that the discard rate after recovery increased from 12% in 1999 to 16% in 2008.…”
Section: Figure 9 Traumatic and Cerebrovascular Accident Causes Of Bmentioning
confidence: 90%